A silent folks: a modern lore preserving the indigenous folktales, myths, and legends in the digital era/ Sharina Saad, Rafidah Amat and Shafila Subri - Saad, Sharina; Amat, Rafidah; Subri, Shafila (Universiti Teknologi MARA, Perak, 2023)
Innovations in second language teaching are desirable because such practices will help to maintain students' interest and motivation in the classroom. Various research has reported the significance of incorporating stimulating reading texts in ESL classrooms. This paper aims to report how innovative ideas on using reading texts which are based on the tales of indigenous people in Malaysia can leave significant impact in an ESL classroom. This innovation project was in the form of a project work given to a group of 30 diploma students undergoing a proficiency class. Reading is one of the main components in the syllabus. One of the subcomponents in reading for this subject is to read, understand, and provide personal responses to short stories. The students were asked to read a few ghost stories based on the lives of Semai people from a book entitled The Myths of Semai prior to their folktales project. The project required the students to retell the story in the form of animated videos. They made story boards to help dramatize the tales and then used video editing apps to compile the story boards into videos of the chosen folktales. They played the videos in class and uploaded them to YouTube for other ESL learners. At the end of the project, students were asked to write a reflective journal about their learning experiences with Semai folktales. The responses were analysed based on the emerging themes which occur in the students' reflections. The findings on this innovative project should contribute to deeper understanding on how animating the folktales can impact ESL students' learning and how using the stories from indigenous people can enhance cross-cultural awareness and acceptance of different traditions.